Pupuk Organik Cair (Poc) dari Limbah Cair Tahu dengan Dekomposer Bongkol Pisang Dalam Pertumbuhan Tanaman Pokcay - Dwi Probowati Sulistyani; Adipati Napoleon; Agus Hermawan; Bakri Bakri; Warsito Warsito; M Farrel Rayhan Riza (xxxx-xxxx, 2023)
Sulistyani DP, Napoleon A, Hermawan A, Bakri B, Warsito W, Riza MFR.  2022. Liquid organic fertilizer (Poc) from tofu liquid waste with banana hump decomposer in pokcay plant growth. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang  27 Oktober 2022. pp. 129-135.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Tofu liquid waste can be used as a new alternative that can be used as liquid organic fertilizer because in the tofu liquid waste it has various nutrients needed for the plant growth process. Based on the research, it shows that the nutrient content in tofu liquid waste before and after liquid fertilizer is made does not meet the standard of liquid fertilizer. To improve the quality of tofu liquid waste as liquid fertilizer, one of them is the addition of local microorganisms (MOL) from banana hump. The specific purpose of the study was to determine the effect of liquid organic fertilizer from tofu liquid waste with the addition of a banana hump decomposer on pokcay plants. Liquid organic fertilizer is one of the efforts to improve the physical and chemical properties of the soil, one of which is Ultisol, so it is expected to increase the growth of pokcay plants to be applied. Ultisols include soils that have very low nutrients and high soil acidity. Poor macronutrient content. Therefore, researchers made efforts so that ultisols could increase the availability of soil nutrients. Liquid organic fertilizer has many advantages, namely the ease of application to soil and plants, which only needs to be watered. The results showed that there was an effect of the dose of liquid organic fertilizer sprinkled on the soil planted with pokcay on the growth, namely plant height, number of leaves, leaf green level, wet weight and dry weight.